Analysis of Extrusion Blow Molding Machine Maintenance Planning with Reliability Centered Maintenance and IRRO Method - Pratama, Mohammad Bintang Rizqi; Puspitasari, Etik (Jurnal Sistem Teknik Industri, 2024)
High demand for plastic products from year to year creates the need for plastic molding machines that can mass produce plastic products. An example of a plastic molding machine used at PT. X is a VK type extrusion blow molding (EBM) machine. Based on data from PT. X, the downtime of the VK type EBM machine reached 215.74 hours in 2021-2023. Therefore, improvements are needed in the machine maintenance management system. The purpose of this research is to determine the critical components, determine the reliability value of the critical components, and also establish a preventive maintenance schedule along with a cost budget plan for each critical component of the VK type extrusion blow molding machine at PT. X to increase the effectiveness of existing production activities. The method used is Reliability Centered Maintenance (RCM) with the application of RCA and FMEA methods to find critical components, then calculate the reliability of critical components as a reference for making preventive maintenance schedules. The data used are the failure data of VK type EBM machine in 2021-2023 period. The results of this study obtained 4 critical components with a reliability value of 0.5, namely the clamping unit at 210.3149 hours, the cutting unit at 79.9911 hours, the head unit at 677.5324 hours, and the hydraulic unit at 424.1550 hours. Maintenance planning is based on the IRRO (Inspection, Repair, Replace, Overhaul) method. The total maintenance cost for the period 2025 is Rp 35,093,903, which reduces the cost by 8.5% compared to 2023.